Adsorption Study of Herbicide 2,4-Dichlorophenoxy Acetic Acid by a-Alumina Clay - M. Farhan, Ahlam (Asian Journal of Chemistry, 2013)
Adsorption of the herbicide 2,4-dichlorophenoxy acetic acid by a-alumina clay minerals, was investigated. Factors influencing adsorption such as pH of the solution, adsorbent dosage, particle size, herbicide concentration and temperature have been studied. The adsorption process was relatively fast and equilibrium was achieved after 2 h, maximum adsorption of 2,4-dichlorophenoxy acetic acid occurred at around pH = 8. Adsorption equilibrium data could also be described well by Freundlich models at the concentration of 2,4-dichlorophenoxy acetic acid which ranging from (40 to 200) mg L-1. Thermodynamic parameters such as enthalpy change (DHº), free energy change (DGº) and entropy change (DSº) were calculated by kinetic equation.